Antibacterial activity of chemical constituents isolated from Asparagus racemosus - Shah, Muhammad Abdullah; Abdullah, Syed Muhammad; Khan, Muhammad Azim; Nasar, Gulfam; Saba, Irum (Bangladesh Journal of Pharmacology, 2014)
Asparagus racemosus is a medical extensively used in traditional medicine for various disorders including its use in infectious. So far work has been done to identify its active constituents responsible for antiseptic folk use of this plant. In the current investigation, we have made an effort to identify its chemical constituents that might be partly responsible for antimicrobial properties. Extraction and isolation of plant extract lead to isolation of two nor-lignans and two steroidal triterpenes (compound 1 to 4). All compound showed considerable antibacterial activities against E. coli and S. aureus while no significant activity was observed against S. typhi. This study highlighted the potential of A. racemosus to be further explored as a source of bioactive natural products.